2023
DOI: 10.3389/fmed.2023.1072837
|View full text |Cite
|
Sign up to set email alerts
|

Beyond skin white spots: Vitiligo and associated comorbidities

Abstract: Vitiligo is a common depigmentation disorder of an unknown origin characterized by the selective loss of melanocytes, resulting in typical white macules and patches. However, vitiligo is now recognized as more than just a skin disease, what a dermatologist observes as a white spot of skin is just the “tip of the iceberg” of the condition. We attempt to clarify the classification of comorbidities associated with vitiligo from various reviews and reports, and describe their possible pathogenesis. In conclusion, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 123 publications
1
20
0
Order By: Relevance
“…Significant differences in the prevalence of some comorbidities (i.e. thyroid disease, type 1 diabetes, atopic dermatitis, psoriasis and depression with treatment) were observed in patients with vitiligo versus controls, consistent with other studies 3,20,21 …”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Significant differences in the prevalence of some comorbidities (i.e. thyroid disease, type 1 diabetes, atopic dermatitis, psoriasis and depression with treatment) were observed in patients with vitiligo versus controls, consistent with other studies 3,20,21 …”
Section: Discussionsupporting
confidence: 90%
“…thyroid disease, type 1 diabetes, atopic dermatitis, psoriasis and depression with treatment) were observed in patients with vitiligo versus controls, consistent with other studies. 3,20,21 Although approximately 85% of patients with vitiligo had <10% BSA involvement, patients reported moderate vitiligo severity. Vitiligo lesions on visible areas as well as the extent of vitiligo were cited by patients as the biggest contributors towards patient-assessed vitiligo severity.…”
Section: Discussionmentioning
confidence: 99%
“…Hu and Wang reported that pernicious anemia was approximately 1.3% among 300 patients with vitiligo, significantly higher than the expected prevalence of 0.15%. 40 Turkey reportedly has the highest number of people with vitiligo affected by pernicious anemia, with a majority of 8.7%. Gill et al reported that the incidence of pernicious anemia in patients with vitiligo was 0.5% 8 ; however, another study showed no significant association between pernicious anemia and vitiligo.…”
Section: Pernicious Anemiamentioning
confidence: 99%
“…Vitiligo is a skin disorder caused by abnormal melanocytes present outside the skin that affects around 1% of the world's population, with no significant differences according to sex, ethnicity, or geography 1 . Many comorbidities are proposed to be associated with vitiligo, including autoimmune diseases, metabolic syndrome, and psychiatric disorders involving melanocytes 2–4 …”
Section: Introductionmentioning
confidence: 99%
“…1 Many comorbidities are proposed to be associated with vitiligo, including autoimmune diseases, metabolic syndrome, and psychiatric disorders involving melanocytes. [2][3][4]…”
mentioning
confidence: 99%